If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 10 = 6(8x) Reorder the terms: 10 + 8x = 6(8x) Remove parenthesis around (8x) 10 + 8x = 6 * 8x Multiply 6 * 8 10 + 8x = 48x Solving 10 + 8x = 48x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48x' to each side of the equation. 10 + 8x + -48x = 48x + -48x Combine like terms: 8x + -48x = -40x 10 + -40x = 48x + -48x Combine like terms: 48x + -48x = 0 10 + -40x = 0 Add '-10' to each side of the equation. 10 + -10 + -40x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -40x = 0 + -10 -40x = 0 + -10 Combine like terms: 0 + -10 = -10 -40x = -10 Divide each side by '-40'. x = 0.25 Simplifying x = 0.25
| 3k+2k=2+6k | | (x*0.75)+(5*0.25)=4 | | -2x^2-3x+54=0 | | -2x-3x+54=0 | | -3+7k=1+8k | | Cos(x)+7x=0 | | 100x^2-x-10=0 | | 54=89-36y | | m+599.01=686.98 | | -12c^2-38c=-40 | | c-19.2=24.0 | | 11-8n=1-6n | | 7x+3x=77 | | a-108.8=-203.0 | | r^2+3-2=0 | | x^2+nx+3x+3n=0 | | 2x^2-3-5=0 | | m+19.32=23.86 | | x=3(13/12-4) | | 8x+2=7(x-3)+4 | | x^2-dx-cx+dc=0 | | -6+m=-3m+6m | | 2p-6=-12+8p | | 3-6v+6v=15+3v | | 30+4x=6x-35 | | 9x*-12x+4=0 | | -1(x-6)=8x-12 | | 8p-28=-22+9p | | 1000000+1=x | | 32x+8y=5600 | | 5(2m-5)=7-(m+3) | | -5a+6a=-10+3a |